1998
DOI: 10.1074/jbc.273.18.10888
|View full text |Cite
|
Sign up to set email alerts
|

Sulfuryl Transfer: The Catalytic Mechanism of Human Estrogen Sulfotransferase

Abstract: Estrogen sulfotransferase (EST) catalyzes the transfer of the sulfuryl group from 3'-phosphoadenosine 5'-phosphosulfate (PAPS) to 17beta-estradiol (E2). The sulfation of E2 prevents it from binding to, and thereby activating, the estrogen receptor. The regulation of EST appears to be causally linked to tumorigenesis in the breast and endometrium. In this study, recombinant human EST is characterized, and the catalytic mechanism of the transfer reaction is investigated in ligand binding and initial rate experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
238
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(254 citation statements)
references
References 22 publications
13
238
2
1
Order By: Relevance
“…However, when inhibited, the velocity decreased to a plateau rather than to zero. This phenomenon was also shown in a study, which observed partial substrate inhibition for human estrogen sulfotransferase (EST) and estradiol (E 2 ) (Zhang et al, 1998). This indicated that one or more of the kinetic parameters for the reaction were being titrated from one value to another.…”
Section: Liver Size But Not Diet Affects Differences In the Total Amentioning
confidence: 58%
See 1 more Smart Citation
“…However, when inhibited, the velocity decreased to a plateau rather than to zero. This phenomenon was also shown in a study, which observed partial substrate inhibition for human estrogen sulfotransferase (EST) and estradiol (E 2 ) (Zhang et al, 1998). This indicated that one or more of the kinetic parameters for the reaction were being titrated from one value to another.…”
Section: Liver Size But Not Diet Affects Differences In the Total Amentioning
confidence: 58%
“…This indicated that one or more of the kinetic parameters for the reaction were being titrated from one value to another. In the study by Zhang et al (1998), two E 2 were bound to each EST, suggesting that partial inhibition occurred through binding at an allosteric site. From this report, we assumed that HPyS utilized the same mechanism.…”
Section: Liver Size But Not Diet Affects Differences In the Total Amentioning
confidence: 97%
“…Therefore, we tested whether the induction of EST plays a role in the anti-breast cancer effect of TM208. EST shows the highest affinity for E2 and estrone [15] , whereas other SULTs, such as SULT1A1 and SULT2A1, exhibit some affinities for E2 and estrone, which are only found at non-physiological high concentrations [14,41] . Not counting EST, SULT1A1 was reported to play the most crucial role in the sulfation of intratumoral estrogens by its contribution to the conjugation of the metabolites of E2 (such as 4-OH-E2 and 2-methoxy-E2) metabolized by CYP1B1 and 1A1 [14,42] .…”
Section: Discussionmentioning
confidence: 99%
“…However, we once investigated the effect of TM208 on SULT1A1 and SULT2A1 and found that TM208 induced the expression of SULT1A1 more significantly than that of SULT2A1 in both MCF-7 cells and MCF-7 xenograft tumors, but all of the observed increases were less than 4-fold (Figure S1-S2). However, the affinity of estrogen is much higher for EST than for SULT1A1, the K m of which is at the nano-or micromolar level, respectively [15] . Therefore, EST is responsible for the sulfation of intratumoral activated E2, which is why we investigated EST rather than other SULT isoforms in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation